(untitled) (Географический вестник=Geographical bulletin, 2017)
Показано влияние выбросов промышленных стоков Соликамско- Березниковского комплекса на состояние и трансформацию гидрофауны верхней части Камского водохранилища. THE ROLE OF CHEMICAL POLLUTION IN FORMING AND CHARACTERISTICS OF THE KAMA RIVER BASIN’S ICHTHYOFAUNA AROUND INDUSTRIAL COMPLEX OF SOLIKAMSK AND BEREZNIKI The effect of emissions from industrial wastewater of Solikamsk-Berezniki industrial complex on the state and transformation of hydrofauna in upper part of the Kama Water Reservoir is shown.